Ideological roots of the conflict between pro-Kurdish and pro-Islamic parties in Turkey - Dag, Rahman (Cambridge Scholars Publishing, 2017)
The current agenda of international politics is full of headline-grabbing conflicts. This book focuses on one such conflict, namely the Kurdish question in Turkey, with recent peace negotiations between Turkey and the PKK having apparently failed. The pro-Islamic ruling party of Turkey (the AK Party) and the ideologically leftist pro-Kurdish parties are the key determinants of this conflict. Their historical development since the inception of modern Turkey is discussed here to demonstrate the similarities and differences between these oppositional social and political groups. In this sense, th.